1995
DOI: 10.1074/jbc.270.18.10800
|View full text |Cite
|
Sign up to set email alerts
|

The Proto-oncogene Product c-Cbl Becomes Tyrosine Phosphorylated by Stimulation with GM-CSF or Epo and Constitutively Binds to the SH3 Domain of Grb2/Ash in Human Hematopoietic Cells

Abstract: Granulocyte-macrophage colony-stimulating factor (GM-CSF) and erythropoietin (Epo) are hematopoietic growth factors that regulate proliferation and differentiation of hematopoietic cells. They elicit and control a cascade of biochemical events, the earliest of which is tyrosine phosphorylation of several cellular proteins. Grb2/Ash is composed of SH2 and SH3 domains. The SH2 domain binds to tyrosine-phosphorylated proteins, and the SH3 domains bind to proteins containing proline-rich regions. It is considered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
156
0

Year Published

1996
1996
1998
1998

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 182 publications
(164 citation statements)
references
References 40 publications
8
156
0
Order By: Relevance
“…In this regard, Grb2 appeared as a good candidate able to connect the multimolecular complex nucleated by c-Cbl, since (1) Grb2 and c-Cbl have been shown to form stable complexes in HL-60 and Jurkat cells, via the Nterminal SH3 domain of Grb2 and the proline-rich motif of the C-terminus of c-Cbl (Donovan et al, 1994;Rivero-Lezcano et al, 1994) and (2) human CSF-1R harbors a docking motif for Grb2 SH2 domain on Tyr 699 (Tyr 697 for murine) (Van Der Geer and Hunter, 1993). In fact, when endogenous Grb2 was immunoprecipitated from c-FmsCHO cells, a signi®cant amount of c-Cbl was recruited in the pellet, even in the absence of CSF-1, indicating that Grb2 was constitutively associated with c-Cbl, in agreement with a previous report (Odai et al, 1995). CSF-1R was also found to interact with Grb2 only in the presence of CSF-1, thus supporting the idea that Grb2 could connect c-Cbl to the autophosphorylated CSF-1R.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In this regard, Grb2 appeared as a good candidate able to connect the multimolecular complex nucleated by c-Cbl, since (1) Grb2 and c-Cbl have been shown to form stable complexes in HL-60 and Jurkat cells, via the Nterminal SH3 domain of Grb2 and the proline-rich motif of the C-terminus of c-Cbl (Donovan et al, 1994;Rivero-Lezcano et al, 1994) and (2) human CSF-1R harbors a docking motif for Grb2 SH2 domain on Tyr 699 (Tyr 697 for murine) (Van Der Geer and Hunter, 1993). In fact, when endogenous Grb2 was immunoprecipitated from c-FmsCHO cells, a signi®cant amount of c-Cbl was recruited in the pellet, even in the absence of CSF-1, indicating that Grb2 was constitutively associated with c-Cbl, in agreement with a previous report (Odai et al, 1995). CSF-1R was also found to interact with Grb2 only in the presence of CSF-1, thus supporting the idea that Grb2 could connect c-Cbl to the autophosphorylated CSF-1R.…”
Section: Discussionsupporting
confidence: 90%
“…In as much as (1) the human CSF-1R harbors the consensus sequence responsible for the docking of the Grb2-SH2 domain on Tyr 699 (Van Der Greer and Hunter, 1993), and (2) it has been shown that the SH3 domain of Grb2 associated constitutively to the prolinerich region of c-Cbl (Odai et al, 1995), we considered the possibility that Grb2 might bridge the CSF-1R and the cCbl/Crk-II complex. Lysates from unstimulated or CSF-1-stimulated c-FmsCHO cells, untreated or boiled in 1% SDS were diluted tenfold in LB then precipitated with GST-Crk-SH2 and ®nally reprobed with anti-Grb2 antibodies.…”
Section: Grb2 Connects the C-cbl/crk-ii Complex To The Activated Csf-1rmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously we have shown that Shc is a substrate of LTK, which binds to the NPXY sequence at the carboxyl terminal domain (amino acids 859 ± 862) and connects Grb2 and LTK (Ueno et al, 1995). Because c-Cbl is known to associate with Shc and Grb2 (Odai et al, 1995;Fukazawa et al, 1996;Panchamoorthy et al, 1996), we hypothesized that tyrosine 862 is critical for c-Cbl phosphorylation. To test this, we examined if several mutant EL receptors can phosphorylate c-Cbl.…”
Section: The Survival Signal Of Ltk Is Sensitive To Wortmanninmentioning
confidence: 94%
“…Cbl lacks a de®ned catalytic domain but is rapidly phosphorylated on tyrosine residues following the stimulation of a wide range of cell surface receptors which include growth factor receptors, immunoglobulin receptors, antigen receptors and integrin receptors (Donovan et al, 1994;Tanaka et al, 1995;Galisteo et al, 1995;Bowtell and Langdon, 1995;Odai et al, 1995;Marcilla et al, 1995;Wang et al, 1996;Cory et al, 1995;Kontani et al, 1996;Ojaniemi et al, 1997). Indeed in many cell types Cbl appears to be one of the most prominent and rapidly phosphorylated substrates of protein tyrosine kinases (Andoniou et al, 1994;Donovan et al, 1994;.…”
Section: Introductionmentioning
confidence: 99%